Intercultural Communication Development in Maritime English Professional Communication Competence - Tristanti; Jin Chul Choi; Fauzan Atsari (PT. Global Research Collaboration, 2026)
This study investigates how intercultural communication development can be integrated into Maritime English professional communication competence within Indonesian maritime vocational education. Employing a qualitative design, semi-structured interviews were conducted with 12 maritime communication experts, 18 maritime English lecturers, and 15 recent maritime graduates from three maritime polytechnic institutions. Data were analyzed through thematic analysis, cross-group comparison, and narrative synthesis. The findings identify five thematic dimensions: multilingual professional communication demands, culturally situated discourse competence, multimodal instructional integration, industry-aligned communicative assessment, and intercultural experiential learning gaps. Cross-group analysis revealed that experts prioritized regulatory and operational communication standards, lecturers emphasized pedagogical constraints in teaching cultural dimensions, and graduates reported persistent inadequacy in real-world intercultural maritime encounters. The study contributes a conceptually grounded framework for embedding intercultural communication within Maritime English curricula, arguing that professional communication competence in maritime contexts requires the integration of linguistic, discursive, cultural, and situational knowledge dimensions beyond conventional English for Specific Purposes approaches. These findings suggest that future research should examine the implementation of intercultural communication-based Maritime English curricula, evaluate pedagogical interventions such as simulation and experiential learning, and conduct comparative or longitudinal studies across different maritime education systems to strengthen global understanding of intercultural communication competence in maritime professional education.